Why does the FDIC sue? - Koch, Christoffer; Okamura, Ken (Journal of Corporate Finance, 2019)
Cases the Federal Deposit Insurance Corporation (FDIC) pursues against the directors and officers of failed commercial banks for (gross) negligence are important for the corporate governance of U.S. commercial banks. These cases shape the kernel of bank corporate governance, as they guide expectations of bankers and regulators in defining the limits of unacceptable behaviour under financial distress, such as risk shifting. We examine the differences in behaviour of all 408 U.S. commercial banks that were taken into receivership between 2007 and 2012. Sued banks had different balance sheet dynamics relative to those who are not sued in the three years prior to failure. These banks were generally larger, faster growing, obtained riskier funding and tended to underprovision. We find evidence that boards of failing banks respond to litigation by reducing the use of riskier funding in an out-of-sample set of banks. Our results suggest the FDIC does set corporate governance standards for all banks by suing negligent directors and officers.